Regeneração e transformação genética em melão (Cucumis melo L.), cv. Gaúcho - Benemann, Daiane de Pinho (2008)
The objective of this work is to seek a protocol for regeneration of the melon (Cucumis melo L.) cv. Gaucho and subsequent genetic transformation of this fruit. To this end were conducted three experiments. In the first, the cotyledons were divided into 2, 3, 4 and 5 equal parts, and inoculated with MS medium containing 30 g L sucrose, 0.9 mg L-1 BAP, 0.3 mg L-1 ABA and 2.2 g L-1 CaCl2. It was observed that the number of cuts not influenced the percentage of explants regenerated. In the second experiment, using the same means of cultivation of the previous experiment, the cotyledons were submitted to different densities of flow of photons. It was found that the regenerative process was not affected by the absence or presence of light (2 and 21 μmol m-2 s-1), but when the explants remained in the dark had greater formation of callus. In the third experiment sought to establish conditions for seed germination and its effect on the regeneration under different concentrations of BAP. It was the highest rate of explants regenerated lower when the period of germination in the middle and lower the concentration of BAP in the regenerative. After obtaining the protocol for regeneration, was conducted test of sensitivity of explants the selection of antibiotic, setting up the concentration of 75 mg L-1, kanamycin as ideal to select the cells transformed. For the regeneration of the shoots explants were cultivated in MS medium containing 0.9 mg L-1 BAB, 0.3 mg L-1 ABA, 2.2 g L-1 CaCl2, 75 mg L-1 kanamycin and 250 mg L-1 cefotaxime. For the genetic transformation was used Agrobacterium tumefaciens LBA 4404, with a clone of ACC oxidase in antisense orientation, called pAP4as. However, it was not confirmed by inserting the sequence, the PCR test, the tissue analyzed. It was found that these studies were not described with Agrobacterium efficient to obtain seedlings containing the antisense gene of ACC oxidase. It was found that these studies were not described with Agrobacterium efficient to obtain seedlings containing the antisense gene of ACC oxidase.